The Impact of Oil and Gas Exports on Indonesia's Foreign Exchange Reserves from 2014 to 2022 - Husaini, Fauzan; Fitri, Fitri; Ramdani, Eggy Armand; Iswanto, Pepe (Syari'ah Economics, 2023)
International trade can affect economic growth, create jobs, distribute income, and affect the country's foreign exchange reserves. One of the efforts to increase the country's foreign exchange reserves is to increase the number of exports. This study uses a multiple linear regression analysis method using time-series data. The classical assumption test methods used in this study include normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. This research was carried out by statistical tests using Eviews-12 software. The statistical tests carried out included the t test (partial), the F test (simultaneous), and the determination coefficient analysis. The research data was sourced from Bank Indonesia and the Central Statistics Agency for the period 2014-2022. The results of the study show that partially the oil and gas export variable have a negative effect on Indonesia's foreign exchange reserves in 2014-2022. Meanwhile, the non-oil and gas export variable has a positive effect on Indonesia's foreign exchange reserves in 2014-2022. The results of the study also show that the variables of oil and gas exports and non-oil and gas exports together affect Indonesia's foreign exchange reserves in 2014-2022 by 72.62%.